Migration of Bisphenol A from Canned Sardines into Food Simulants: Effect of Temperature and Concentration - Alfin Ghanesa Putra; Sutanto Sutanto; Muhammad Fathurrahman (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2025)
Epoxy resin coatings containing Bisphenol A (BPA) are widely used in canned food packaging, including sardine cans. They may pose a risk of chemical migration into food products under specific conditions. This study aimed to evaluate BPA migration into food simulants, acetic acid (1%, 3%, and 10%) and ethanol (10%, 20%, and 50%), at three temperatures (60 °C, 100 °C, and 121 °C). Migration levels were quantified using High-Performance Liquid Chromatography (HPLC) with UV-Vis detection. Preliminary analysis of five sardine can brands revealed BPA concentrations ranging from 0.0052 to 0.0487 mg/kg. Results demonstrated a significant increase in BPA migration with both simulant concentration and temperature. In ethanol, migration increased by 437% when the concentration rose from 10% to 50% at 121 °C, while a 92% increase was observed in acetic acid from 1% to 10% under the same conditions. Temperature had a more pronounced effect: BPA migration in 20% ethanol rose by 3,714% between 60 °C and 121 °C. Migration in 3% acetic acid increased from undetectable to 0.1515 mg/kg across the same temperature range. These findings indicate that BPA migration is significantly influenced by simulant type, concentration, and temperature, underscoring the necessity for stringent control over packaging conditions to ensure food safety.